Hubungan Faktor Maternal terhadap Posisi pada Waktu Persalinan Kala II dengan Kejadian Ruptur Perineum - Wa Ode Hajrah; Niken Purbowati; Novia Nuraini (Jurnal Bidan Cerdas, 2019)
erineal rupture needs attention because it can cause dysfunction of the female reproductive organs, as a source of bleeding, a source, or a way in and out of infection, then it can cause death due to bleeding or sepsis. About 85% of Women who delivery vaginally experience perineal rupture, in the age group 25-30 years 24%, while in maternal age 32-39 years by 62%. In Asia, perineal rupture is also a problem in society, 50 % of the world's occurrence is in Asia. The study aims to determine the relationship of maternal factors to the position of the second stage labor and perineal rupture occurrence. This research applied a descriptive-analytic method using a cross-sectional research design. The research sample was 102 respondents, accidental random sampling, which was all labor with perineal rupture in July to November 2018. Statistical tests used chi-square. The results of perineal rupture with maternal age was p-value 0.042 (p <0.05), perineal rupture with maternal parity was p-value 0.01 (p <0.05). Suggestions for various maternal positions in maternity and ANC classes to prevent perineal rupture.